RECLAIM: Toward a New Era of Refurbishment and Remanufacturing of Industrial Equipment - Zacharaki, Angeliki; Vafeiadis, Thanasis; Kolokas, Nikolaos; Vaxevani, Aikaterini; Xu, Yuchun; Peschl, Michael; Ioannidis, Dimosthenis; Tzovaras, Dimitrios (Frontiers in Artificial Intelligence, 2021)
Refurbishment and re-manufacturing are the industrial process whereby used products or parts that constitute the product are restored. Re-manufacturing is the process of restoring the product or part functionality to “as-new” quality and refurbishment is the process of restoring the product or part to “like-new”, but the process will not be as thorough as re-manufacturing. Within this context, the EU funded project RECLAIM presents a new idea on refurbishment and re-manufacturing based on big data analytics, machine learning, predictive analytics and optimization models using deep learning techniques and digital twin models with the aim of facilitating the stakeholders to make informed decisions about whether to re-manufacture, upgrade or repair heavy machinery that is towards its end-of-life. Also, provide novel strategies and technologies that enable the re-use of industrial equipment in old, renewed and new factories, aiming to save valuable resources by re-cycling equipment and to use it in a different application, instead of discarding it after use. The vision of RECLAIM project is to demonstrate technologies and strategies in support of a new paradigm for the management of large industrial equipment that approaches the end of its design life. This paradigm will substantially reduce the opportunity cost of retain strategies (both money-wise and resource-wise) by allowing relatively-old equipment that faces the prospect of decommissioning to reclaim its functionalities and role in the overall production system.